2016
DOI: 10.1007/978-3-319-39745-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts—Coastal Ecosystems

Abstract: This chapter examines the impacts of climate change on the natural coastal ecosystems in the North Sea region. These comprise sandy shores and dunes and salt marshes in estuaries and along the coast. The chapter starts by describing the characteristic geomorphological features of these systems and the importance of sediment transport. Consideration is then given to the role of bioengineering organisms in feedback relationships with substrate, how changes in physical conditions such as embankments affect coasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 180 publications
1
10
0
Order By: Relevance
“…Soil formation in a salt marsh occurs by accumulation of sediment and plant biomass, and allows marshes to accrete vertically in response to rising sea levels (Bakker et al . ; Boyd & Sommerfield ). Our analyses revealed that grazers compact the sediment and reduce AGB, but this did not translate into a significant overall reduction in accretion rates (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil formation in a salt marsh occurs by accumulation of sediment and plant biomass, and allows marshes to accrete vertically in response to rising sea levels (Bakker et al . ; Boyd & Sommerfield ). Our analyses revealed that grazers compact the sediment and reduce AGB, but this did not translate into a significant overall reduction in accretion rates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, accretion rates are highly context‐dependent, driven by local factors such as sediment input (Bakker et al . ), which may mask the effects of grazing in some studies. In light of the results of our coded meta‐analysis (11 out of 13 entries presented negative results for accretion), we recommend further research on the mechanisms and context‐dependency of livestock impacts, as reduced capacity for vertical accretion could lead to submergence under rising seas with concomitant loss in the provision of all services.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they often grow in an undulating landscape with variable exposure and slope, resulting in a high variability of microclimates. Thanks to these features, they host a large variety of species, often rare, endemic or endangered, and a very high number of different plant communities (Bioret, Lazare, & Géhu, ; Del Vecchio, Giovi, Izzi, Abbate, & Acosta, ; Del Vecchio, Mattana, Acosta, & Bacchetta, ; Martínez et al., ), which, alongside serious anthropogenic threats, makes them habitats of major conservation concern (Bakker et al., ; Janssen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Intergovernmental Panel on Climate Change Fifth Assessment Report (IPCC AR5; Church et al, 2013), SLR is predicted to increase by 30-100 cm by 2100 and will thus reshape coastal wetlands globally. This is of particular concern in all those areas (e.g., the Mississippi Delta or the Venice Lagoon) where sediment accretion rates are too low as to compensate for relative SLR (Bakker et al, 2016). Here, the extensive die-back of marsh vegetation (Kearney, Rogers, Townshend, Rizzo, & Stutzer, 2002) or habitat loss (Mander, Cutts, Allen, & Mazik, 2007;Pye & Blott, 2006) will affect other population of dependent organisms (Fujii & Raffaelli, 2008;Galbraith, Jones, Park, Clough, & Herrod-Julius, 2002;Hughes, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the extensive die-back of marsh vegetation (Kearney, Rogers, Townshend, Rizzo, & Stutzer, 2002) or habitat loss (Mander, Cutts, Allen, & Mazik, 2007;Pye & Blott, 2006) will affect other population of dependent organisms (Fujii & Raffaelli, 2008;Galbraith, Jones, Park, Clough, & Herrod-Julius, 2002;Hughes, 2004). In particular, accelerated SLR is likely to affect the salt marsh halophyte vertical distribution: depending on the level of change, some communities may adapt to sea level rise while others may either disappear or migrate inland-provided that there is suitable area inland (Bakker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%